Amnesty petition demanding ceasefire in Gaza, Israel backed by over million signatures - Amnesty International (Amnesty International, 2023)
The world is watching in horror as more and more civilians lose their lives each day amid Israel’s relentless bombardment and ground operations.
Keywords: 2023-10 November

Cambodia: Mass evictions at UNESCO World Heritage site Angkor violate international law - Amnesty International (Amnesty International, 2023)
Cambodian authorities cruelly uprooted families who have lived in Angkor for several generations.
Keywords: 2023-10 November

Amnesty petition demanding ceasefire in Gaza, Israel backed by over million signatures - Amnesty International (Amnesty International, 2023)
The world is watching in horror as more and more civilians lose their lives each day amid Israel’s relentless bombardment and ground operations.
Keywords: 2023-10 November

South Korea: Jail sentence for man who praised North an attack on freedom of expression - Amnesty International (Amnesty International, 2023)
Responding to the sentencing of a South Korean man, Lee Yoon-seop, to 14 months in prison for praising North Korea in a poem, Amnesty International’s East Asia Researcher Boram Jang said: “South Korean authorities must drop all charges against Lee Yoon-seop, who has been sentenced to jail simply for exercising his right to freedom of […]
Keywords: 2023-10 November; Republic of Korea